Dietary Glutamic Acid, Obesity, and Depressive Symptoms in Patients With Schizophrenia - Kumar, Pooja; Kraal, A. Zarina; Prawdzik, Andreas M.; Ringold, Allison E.; Ellingrod, Vicki (Frontiers in Psychiatry, 2021)
Schizophrenia is a lifelong condition associated with several comorbid conditions such as physical illnesses like obesity, as well as co-occurring psychiatric symptoms such as depression. Research regarding susceptibility to some of these comorbidities has primary focused on genetic risks or dysfunction of key neurotransmitter systems and very little work has been done to understand the role of diet. In particular, understanding the role of dietary monosodium glutamate (MSG) on co-morbidities in patients with schizophrenia is important, as evidence suggests MSG may directly influence glutamatergic neurotransmission; a key neurotransmitter related to schizophrenia and its associated co-morbidities. Therefore, the aim of this study was to examine the potential relationship between dietary glutamic acid (a surrogate of MSG intake) and depressive symptomatology in patients with schizophrenia, stratified by obesity status. Subjects included in this analysis, were part of a parent cross sectional study in which they underwent three dietary recalls, which were analyzed using standard protocols outlined as part of the National Health and Nutrition Examination Surveys (NHANES) standardized criteria. Additionally, body mass index (BMI), and Beck Depression Inventory were obtained at this visit. Subjects with a BMI ≥ 30 kg/m2 were included in the obesity group, and the relationship between glutamic acid consumption and BDI scores was analyzed after controlling for age, race, sex, antidepressant and antipsychotic use, and animal and vegetable protein intake which are provide natural forms of dietary glutamic acid. A total of 168 participants were included, of which 42.5% were female and 52.9% were White. The mean BMI for the group as a whole was 33.5 ± 8.7 (kg/m2) and the mean BDI was 14.5 ± 10.7 (range 2-50). No differences were found between obesity groups, other than a greater hyperlipidemia and hypertension. Overall, no relationship was found between dietary glutamic acid and BDI scores, when taken as a whole. However, for non-obese participants, diets higher levels of glutamic acid were associated with greater depression symptomatology (p = 0.021). These preliminary results indicate a possible correlation between dietary glutamic acid a depressive symptoms in non-obese patients with schizophrenia, although further research is needed to specifically examine this relationship.